Study of the radiochemical and thermal conversions mechanism in products of processing of grapes - Dikiy, N.P.; Dovbnya, A.N.; Kutovoy, V.A.; Kutovoy, S.V.; Medvedeva, E.P.; Medvedev, D.V.; Borisenko, N.V. (Вопросы атомной науки и техники, 2005)
The extraction of biologically active substance was carried out with help of combination of the physical factors: various conditions of temperature (40, 50, 60°С) and pressure of vacuum drying (8, 14, 16 mm Hg), and also various radiation doses by electrons with energy 12 МeV (10, 20, 40 kGy). The investigations of dynamics of definition of extract acidity and formation level of intermediate active products are carried out. It was established that the modification of properties of grape raw material depends on type of grapes, requirements of vacuum drying and radiation dose by electrons.